Alone together : why we expect more from technology and less from each other - Turkle, Sherry (Basic Books, 2011)
In "Alone Together," MIT technology and society professor Sherry Turkle explores the power of our new tools and toys to dramatically alter our social lives. It's a nuanced exploration of what we are looking for--and sacrificing--in a world of electronic companions and social networking tools, and an argument that, despite the hand-waving of today's self-described prophets of the future, it will be the next generation who will chart the path between isolation and connectivity.